Matrix metalloproteinase9 as the protein target in anti-breast cancer drug discovery: an approach by targeting hemopexin domain - Christophorus Fideluno Adhipandito; Diana Putri Kartika Sari Ludji; Eko Aprilianto; Riris Istighfari Jenie; Belal Al-Najjar; Maywan Hariono (SpringerOpen, 2019)
Abstract Background The discovery and development of anticancer still remain a challenge especially regarding the problem of cancer cell selectivity. Matrix metalloproteinase (MMP) was broadly studied as one of the protein targets to stop cancer angiogenesis as well as its cell migration. Main text The MMP degrades extracellular matrix (ECM) such as collagen and gelatin which are important to control the cell migration from one to other sites. In cancer, this cell migration is regarded with metastasis, which is essential for the formation of new blood vessels called angiogenesis. The most common target in MMP, i.e. the catalytic site, is currently reported as being the non-selective target for inhibitor compounds that inhibit all MMPs but is associated with adverse side effects. Hemopexin, especially in MMP9 (PEX9) was found to be different from other domains in the MMP family which could potentially be the next target for anticancer due to the availability of its crystal structure in the Protein Data Bank (PDB). Conclusion The PEX9 crystal structure was resolved as a homodimer connected by a hydrophobic area between two blades along the β-propeller which its structure and function for computational drug modelling can be studied.